Correlation between Extracellular Heat Shock Protein 60 (exHSP60) and Homeostatic Model Assessment of Insulin Resistance (HOMA-IR) in Non Diabetic Men - Meiriza Djohari; Suryani As'ad; Mansyur Arif; Andi Wijaya (The Indonesian Biomedical Journal, 2013)
BACKGROUND: Adipose tissue expansion in obesity leads to abnormal adipocyte function, chronic low grade inflammation, primary reticulum stress, and mitochondrial stress. This induces mitochondrial unfolded protein response (UPRmt) that selectively upregulates mitochondrial chaperone protein. Heat shock Protein 60 (HSP60) is the primary chaperone in mitochondrial matrix. Inflammatory stress promotes HSP60 released from adipocytes and induces insulin resistance. In this study we attempted to investigate the correlation between exHSP60 and HOMA-IR in men with different ranges of waist circumference (WC).METHODS: This study was an observational cross sectional study carried out on 141 non diabetic men, aged 30-55 years old, who were divided into three groups based on WC; WC ≤90 cm, 90 cm < WC ≤ 100 cm and WC > 100 cm. Fasting plasma glucose, triglyceride, HDL-C, hsCRP, HSP60 serum and anti-HSP60 antibody, serum IL-1β serum, insulin, were examined. For statistical analysis, Kolmogorov-Smirnov and Spearman’s correlation analysis were conducted.RESULTS: There were a significant correlation between exHSP60 and HOMA-IR (r=0.281; p=0.041) in WC ≤ 90 cm group; and a negative significant correlation between exHSP60 and HOMA-IR (r=-0.508; p=0.007) in WC > 100 cm group.CONCLUSION: This study showed that there was a dynamic correlation between exHSP60 and HOMA-IR in WC ≤ 90 cm group compared with WC > 100 cm group. We also found inverse correlation patterns between exHSP60 and HOMA-IR, and between anti-HSP60 antibody and HOMA-IR in non diabetic subjects.KEYWORDS: obesity, insulin resistance, mitochondrial stress, exHSP60, hsCRP, HOMA-IR